Analisis Peranan Guru dalam Membentuk Sikap Disiplin Siswa Sekolah Dasar Negeri 1 Kadugede - Anggi Pramowardhani; Mega Katarina Trijayanti (LP2M Universitas Ibrahimy, 2024)
In the learning process, of course learning does not always run smoothly without any obstacles occurring, it is often faced with various obstacles experienced by both teachers and students. One of the obstacles that can cause failure experienced by students in the learning process is the lack of embedded discipline in students at school. Such as students not doing their assignments, talking when the teacher is teaching, making noise in class, walking around in class, students sitting untidy, students disturbing their friends while learning is taking olace. Then, when carriying out the flag ceremony, students joked with their friends, disturbing the solemn atmosphere. Therefore, the teacher’s role is needed in forming students’ disciplinary attitudes. The focus of this research aims to analyze the role of teachers in improving students’ disciplinary attitudes using a qualitative approach. The research techniques used are observation, interviews, and documentation. The data obtained was then analyzed using qualitative descriptive methods, through data collection, data reduction, data presentation and drawing conclusions. The results of this research show that analysis of the teacher’s role can shape students’ disciplinary attitudes at SDN 1 Kadugede. With the role of teacher, students’ disciplinary attitudes become more formed see from the teacher’s role as educator, instructor, mentor, advisor, role model, motivator and the teacher’s role as evaluator. The disciplinary attitude t applied in forming student discipline is obeying school rules, disciplinary behavior in the classroom, discipline in keeping to the schedule and studying regularly. With this disciplinary attitudes, are fromed to be better.